“A Traditional Politician is Boring”: The Search for Political Authenticity in Lithuania through the Lens of Populism - Vaičekauskienė, Giedrė (Information & Media, 2025)
This article discusses the concept of political authenticity and associated issues in the context of populism and the decline of liberal democracy. It initiates a new discussion on political authenticity in the Lithuanian tradition of political communication research by analysing trust and distrust in political leaders from a societal perspective. The article seeks to provide theoretical and empirical answers to questions that explain why populist forces are successful in Western democracies today, and why traditional politicians are defeated or fail to represent their constituents. The article is based on the results of an original focus group study conducted in 2025. Fifteen discussions were held with supporters of the political parties and coalitions that participated in the Lithuanian parliamentary elections of the year 2024. A total of 82 informants participated in the study. Thematic analysis of the qualitative data revealed that Lithuanian citizens, as voters, trust political leaders and consider them authentic, capable of creating social connections through their language, thereby demonstrating charismatic power. In that light, informants explain why populists are interesting. The study indicated significant dissatisfaction with traditional politicians and a lack of authoritative leaders among the diverse voices of democracy who can mitigate dividing lines in Lithuania.
Keywords: political authenticity; populism; political leadership; populist rhetoric; focus group discussions